(3GdfbhO h GdHfhc h GdeUGQa GdeQcRjI (B/s - (3GdMdGb, SYjO SGejs; (3GdYLdhfj, eMeO eMehO s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3JWhQ GdfbhO h GfhGYgG hhXGFagG h CgejJgG GdGbJUGOjI , GdfXe GdfbOjI , GdeUGQja GdJLGQjI h Ndb GdhOGFY , GdGShGb GdfbOjI h GdeGdjI h GOhGJgG , GdfXQjI GdfbOjI GdcdGSjcjI , h GdfXQjI GdcjfRjI , GdfXQjI HYO GdcjfRjI , GdfbhO aj GWGQ GdfXQjI GdfbOjI , GdfXQjGJ GdfbOjI GdeYGUQI , eGgjI GdeUQa GdeQcRj h fTCJg , GdHfhc GdeQcRjI h GUOGQ GdYedI , GdHfc GdeQcRj h GdQbGHI Ydi GdGFJeGf , GdhXGFa GdGNQi ddHfhc GdeQcRjI , WHjYI GdJVNe h CfhGYg h bjGSg , eOGQS h fXQjGJ GdJVNe , BKGQ GdJVNe h eNGWQg , eYGdLI GdJVNe , GdSjGSI GdfbOjI h GdfTGW GdGbJUGOj , hSGFd GdSjGSI GdJbOjI , GdSjGSI GdeGdjI , JfSjb GdSjGSI GdfbOjI h GdSjGSI GdeGdjI , SYQ GdUQa GdGLfHj, SYQ GdUQa h ejRGf GdeOahYGJ , SYQ GdUQa , ejRGf GdeOahYGJ h GdONd Gdbhej (B.s
(3eQGLY U(B.319.s
Keywords: (3GdCShGb GdeGdjIs; (3GdHfhcs; (3GdeUGQa GdeQcRjIs; (3GdfbhOs